Perbandingan Hasil Tangkapan Udang Putih (Penaeus Merguiensis de Man 1888) di Perairan Pantai Kumbe Dan Kaiburse - Sutanti Sutanti; Ranti Duwi; Edy H.P Melmambessy; Bonny Lantang (Universitas Musamus, Merauke, Papua, 2019)
The study aims to determine the comparison of Penaeus merguiensis catches and the influence of environmental factor on Penaeus merguiensis catches in the waters of the Kumbe and Kaiburse beaches in the Malind District of Merauke Regency. This research was conducted from May-June 2019. The method used in this research is survey method. Data analysis to determine the effect of environmental factor on the presence of Penaeus merguiensis was carried out t-test using SPSS 22 program. The results obtained in the comparison of Penaeus merguiensis catches at 115.2 kg Kumbe while at Kaiburse at 123.8 kg. The total catch of Penaeus merguiensis in Kumbe and Kaiburse is 239.0 kg. The results showed that the temperature of theb waters affect the catch of Penaeus merguiensis.